Burundi : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility; Staff Report and Press Release. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the Third Review Under the Extended Credit Facility (ECF) for Burundi. In a difficult post-conflict environment, performance on the ECF-supported program was satisfactory. All quantitative performance criteria for end-September 2009 were met, and structural reforms are on track. The closing of off-budget accounts constitutes a major step toward establishment of a single treasury account. The program for 2010 seeks to consolidate economic stability and support gradual recovery of the economy. IMF staff recommends completion of the Third Review based on Burundi's performance and the strength of the program.